Universal access to e-mail : feasibility and societal implications - Anderson, Robert H. (Robert Helms), 1939-; Bikson, Tora K., 1940-; Law, Sally Ann.; Mitchell, Bridger M.; Kedzie, Christopher R.; Keltner, Brent; Panis, Constantijn W. A.; Pliskin, Joel Alan.; Srinagesh, Padmanabhan; Rand Corporation; John and Mary R. Markle Foundation (Santa Monica, CA : RAND, 1995)
E-mail has swept the communications and information world, providing near-instantaneous global information and data exchange. However, this revolution primarily benefits an information elite: those with access to and knowledge about computers and e-mail. The diverging trends in access based on income and education are placing significant groups of current and next-generation U.S. citizens at a serious disadvantage in relevant job-related skills and in access to social programs and information. Information haves may leave the have-nots further behind, unless concerted efforts are made to provide all citizens with access to the technology. This report gives serious consideration to closing the access gap. The study details the benefits--on the personal as well as national and global level--of e-mail access. It recommends support of a U.S. policy of universal access and addresses the technical and economic aspects of putting such a policy into operation.
"Center for Information Revolution Analyses."
Includes bibliographical references (p. 249-267).
Also available on the internet via WWW.
Keywords: Electronic mail systems -- Government policy -- United States; Electronic mail systems -- Social aspects -- United States